2022
DOI: 10.1097/tp.0000000000004213
|View full text |Cite
|
Sign up to set email alerts
|

Right Lobe Versus Left Lobe Living Donor Liver Transplantation: A Systematic Review and Meta-analysis of Donor and Recipient Outcomes

Abstract: Background. Living donor liver transplantation (LDLT) is an established treatment for advanced liver disease. Whether right lobe (RL) or left lobe (LL) LDLT provides the best outcomes for donors and recipients remains contentious. Methods. MedLine, Embase, PubMed, and Cochrane Central were searched to identify studies comparing RL- and LL-LDLT and reporting donor and/or recipient outcomes. Effect sizes were pooled using random-effect meta-analysis. Meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…For example, a systematic review suggested that left hemiliver donors experience fewer complications than right hemiliver donors, whereas left hemiliver recipients had a similar outcome to right hemiliver recipients. 31 This leads to the suggestion to prefer a left hemiliver graft when feasible. 32 In our study, while right and left hemiliver recipients indeed disclosed comparable mortality, graft loss, and need for redo-LT rates at 1-year, left hemiliver recipients developed more severe complications with a higher CCI ® score which is also well reflected in the longer ICU and hospital stay, compared with right hemiliver recipients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a systematic review suggested that left hemiliver donors experience fewer complications than right hemiliver donors, whereas left hemiliver recipients had a similar outcome to right hemiliver recipients. 31 This leads to the suggestion to prefer a left hemiliver graft when feasible. 32 In our study, while right and left hemiliver recipients indeed disclosed comparable mortality, graft loss, and need for redo-LT rates at 1-year, left hemiliver recipients developed more severe complications with a higher CCI ® score which is also well reflected in the longer ICU and hospital stay, compared with right hemiliver recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Because the use of left hemiliver remains low, direct comparison between right and left hemiliver LDLT is scarce and unconvincing in the literature. For example, a systematic review suggested that left hemiliver donors experience fewer complications than right hemiliver donors, whereas left hemiliver recipients had a similar outcome to right hemiliver recipients 31 . This leads to the suggestion to prefer a left hemiliver graft when feasible 32 .…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of the journal, Acuna et al performed a meta-analysis to compare the outcomes of right and left donation on donor and recipient outcomes. 7 Overall, they found fewer complications among left lobe donors, with notably more high-grade complications among right lobe donors, although overall mortality was the same (too rare to reliably compare in both groups). With respect to recipients, the authors observed that overall patient and graft survivals were comparable, although small for size syndrome was more common among left lobe recipients.…”
mentioning
confidence: 90%
“…The comparable outcomes between RL and LL donation, has prevented a “left-shift,” with RL-LDLT still preferred because of recipient operation being technically less challenging, with less vascular complications, better regeneration, and overall better short- and long-term graft and patient survival. 60 This can be explained by the good outcomes from RL grafts providing minimum absolute graft weight of 650 g, despite a GRWR of <0.8. 61…”
Section: Donor Selectionmentioning
confidence: 99%
“…A recent meta-analysis of 25 230 donors, reported RL donors were more likely to experience any complication (RR = 1.35; 95% confidence interval [CI], 1.18-1.59; I 2 = 53%; 28 studies; 12 359 patients), major complication (RR = 1.63; 95% CI, 1.30-2.05; I 2 = 19.4%; 22 studies; 13 075 patients), and stayed longer in hospital (SMD, 1.48; 95% CI, 1.20-1.83; 20 studies; 9823 patients). Importantly, because of their larger graft volume, average mean RL graft 675 g (range, 461–994 g) versus LL graft 437 g (range, 283–519 g), the RL-LDLT recipients were less likely to develop SFSS (RR = 0.47; 95% CI, 0.30-0.74; I 2 = 0%; 9 studies; 1829 patients) 60 (Table 1).…”
Section: Donor Selectionmentioning
confidence: 99%